EPIDEMIOLOGY OF HYPERTENSION IN AN URBAN AREA DEPENDING OF A TERTIARY HOSPITAL. (June 2018) - García, F. Martínez; Pichler, G.; Usó, R.; Ruíz, A.; Saurí, I.; Solaz, E.; Calaforra, O.; Cacheiro, J.; Redon, J.
Abstract : Objective: Electronic Health Recordings are useful tools for monitoring chronic diseases. However, there are potential issues regarding the veracity of the information. Our objective was to know the epidemiological data for hypertension in our health department using the EHR and our own data from a specialised Hypertension Unit. Design and method: Information regarding the status of hypertension in the dependence area of a tertiary hospital of Valencia (Spain) was reviewed, as well as those obtained from the corresponding specialized Hypertension Clinic. Results: The total population ascribed to the tertiary hospital was 341.340 inhabitants. The structure of our Health Department and its demographic characteristics are shown in Figure 1. Figure. No caption available. Of those, one of the many different diagnostics related to hypertension was present in 139.899, which means a prevalence of almost 41%. The main codified diagnosis was "Essential Hypertension" (almost 47.5%), follow by "non-specified hypertension" (35.5%), "benign hypertension" (14%) and "malign hypertension" (1.5%). There were other 25 different diagnosis, which had very low prevalence (less than 1%) and mainly related with hypertensive kidney/heart organ damage. From April 2014 to June 2017, 2296 subjects were attended in the Hypertension Unit. The majority of individuals had only one (28.2%) or two visits (34.6%). There were 495 (21.6%) with three, 236 (10.4) with four, 75 (3.27%) with five, 24 (1%) with six, 14 (0.6%) with seven and 10 patients with 10 visits. Roughly, around 37% patients had criteria to be follow in a specialized unit. The average age of those, was 60 year, 46% women, 87% dyslipidemics, 52% with obesity, 37% diabetics, 23% current smokers, 20% in secondary prevention, 10% with resistant hypertension, 20% with microalbuminuria and 12% with LVH. Conclusions: In order to be useful, EHR integrating primary and specialized care should be implemented to better reflect the grade of control and the associated organ damage.